Differential involvement of left and right frontoparietal areas in visuospatial planning: An rTMS study. (January 2020) - Basso, Demis; Saracini, Chiara
Abstract: The planning process consists of pre-determining an ordered series of actions to accomplish a goal. Previous research showed that the left prefrontal cortex (PFC) is likely to create the strategy for a plan, while the right PFC could be relevant for its update. These roles for the two PFCs need to be ascertained for visuospatial planning, whether communalities or differences exist with other planning tasks. Moreover, the contribution of the posterior parietal cortex (PPC) to planning still lacks evidence. Online repetitive transcranial magnetic stimulation (1 Hz) was used, and 32 participants were involved in the visuospatial planning task in a within-subject design to inhibit either the frontal or the parietal cortex of either the left or the right hemisphere. The goal consisted of evaluating the contribution of these cortical regions, also controlling for gender, in a computerized version of the travelling salesman problem (TSP), the "Maps" task. The results showed that all the stimulated sites produced significant differences in their involvement, reflected in several parameters (such as initial planning and execution times, strategies and heuristics used), with respect to the control group. The roles for the two PFCs were generally confirmed in all measures except path length, while the contribution of the PPC emerged throughout the measures related to the ongoing execution. We concluded that the results obtained with the TSP paradigm were consistent with results obtained using other tasks used to study the planning process (such as the Tower of London) for the evaluation of PFC contribution. In addition, we showed that the contribution of the PPC to the planning process has probably been underestimated. Highlights: Stimulating the right PFC with rTMS confirmed its role in monitoring and updating visuospatial planning. Left PFC stimulation affected the initial planning process and increased execution times. Stimulation of both parietal areas reduced execution times and strategies with changes.